PRODUKTIVITAS BURUH TANI PENYADAP KARET RAKYAT DAN STRUKTUR PENDAPATAN RUMAH TANGGANYA (DESA AIR SEKAMANAK KECAMATAN KETAHUN KABUPATEN BENGKULU UTARA) - Syahfrudin, Ridlo; Sukiyono, Ketut; Yuliarti, Ellys (Jurnal AGRISEP, 2011)
The research was conducted in the Air Sekamanak village ketahun in North Bengkulu. The research location is determined purposively with consideration the village population moyority  are farming rubber 75%. The purpose of this study to: 1) Estimate the level of productivity of rubber tappers, 2) Investigate the structure of rubber tappers household income. The object of research is the variables that relate to activities that tap-time employment, production, costs and revenues. The results of this study with the conclusions 1) Average labor productivity of agricultural workers in the rubber tappers of the Air Sekamanak village 3,822 Kg/wacth. 2) The average income of households in the Air Sekamanak village Rp 1.9466.490,476/month. The average income derived from farm laborers for the rubber tappers Rp 1.720.740,476/farming/month its contribution to household income by 88,402%. While the average income derived from activities outside of tapping rubber laborers Rp 225.750/month. This means that contribution to household income is about 11,598%.